Global legislation for food packaging materials - Rijk, Rinus; Veraart, Rob (Wiley-VCH Verlag, 2010)
Providing a global overview of legislation in all major countries, this volume contains the information vital for manufactures of food contact materials and food producers, facilitating a comparison of the requirements and making mutual requirements easier to identify. It covers not only plastics but also other food contact materials.